2019
DOI: 10.1016/j.bjpt.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle training versus no treatment, or inactive control treatments, for urinary incontinence in women: a cochrane systematic review abridged republication

Abstract: Background: Pelvic floor muscle training is the most commonly used physical therapy treatment for women with urinary incontinence. Objectives: To assess the effects of Pelvic floor muscle training for women with urinary incontinence in comparison to a control treatment and to summarize relevant economic findings. Methods: Cochrane Incontinence Group Specialized Register (February 12, 2018). Selection criteria: Randomized or quasi-randomized trials in women with stress, urgency or mixed urinary incontinence (sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 45 publications
3
50
0
3
Order By: Relevance
“…Similar to the main findings of three included studies using PFMT, Cacciari et al [ 69 ] indicated that PFMT can reduce the number of urinary leakage episodes and improve all types of urinary incontinence issues as well as QoL in women with urinary symptoms. Furthermore, Carcelen-Fraile et al [ 58 ] found that PFMT was the most common type of exercise used in studies investigating the effects of physical exercise programs on quality of sexual life related to menopausal symptoms, and it seems most beneficial for sexual function in perimenopausal or postmenopausal women.…”
Section: Discussionsupporting
confidence: 63%
“…Similar to the main findings of three included studies using PFMT, Cacciari et al [ 69 ] indicated that PFMT can reduce the number of urinary leakage episodes and improve all types of urinary incontinence issues as well as QoL in women with urinary symptoms. Furthermore, Carcelen-Fraile et al [ 58 ] found that PFMT was the most common type of exercise used in studies investigating the effects of physical exercise programs on quality of sexual life related to menopausal symptoms, and it seems most beneficial for sexual function in perimenopausal or postmenopausal women.…”
Section: Discussionsupporting
confidence: 63%
“…Hypertonia (increased muscle tension at rest), characteristic of the dysfunctions mentioned above, may contribute to the incorrect sliding of actin and myosin myofilaments, responsible for muscle contraction and relaxation, and may disrupt the generation of muscular strength and endurance [ 36 ]. A current, comprehensive review of PFMsT indicates that women with impaired contraction (impaired motor control) are excluded from studies on PFMsT [ 37 ], reinforcing the fact that contraction influences PFM force generation. Thus, can the decrease in the bioelectric activity of PFMs translate into the improvement of their functions and restoration of motor control in the case of various types of pelvic floor dysfunction?…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic floor muscle training (PFMT) is a well-described, effective, and most commonly used method of physiotherapeutic UI treatment which has been recognized and recommended as the first line of conservative SUI treatment [47]. For the first time, PFM exercises were described in 1948 by Arnold Kegel as a behavioral method in the treatment of UI [48].…”
Section: Pelvic Floor Muscle Trainingmentioning
confidence: 99%